IoT-Based Medical Box Improvement for The Elderly Adapting ISO 17025 and Quality of Service - Arum, Dewi Sekar; Kurnianto, Danny; Yusro, Muhammad (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
Elderly is a period characterized by limited movement functions in the body. Elderly with multiple comorbidities have a higher risk of non-adherence because receiving more than one type of drug is more susceptible to skipping medication hours so that the elderly need reminders and drug storage areas to maintain drug quality. The main objective of this research is to emerge the robust medical box which gives notification and could be monitored suited to elderly purposes. This research was carried out with Arduino Uno as the control center of the system and using the ESP8266 Wi-Fi module for internet connection. This system uses a DHT-22 sensor, an HW-201 IR sensor and a servo motor. Tool standardization is also carried out through method validation adapting ISO 17025 and network-related Quality of Service (QoS). The results show that the system can work according to the command with an alarm notification on the android application when the clock shows the time to take medicine. Based on the DHT 22 sensor test, by measuring the temperature and humidity, the bias value is 0.318% and the trueness value is 99.7%. This Medical Box tool also has an acceptance limit precision of 83%. Based on the QoS network testing according to THIPON, the network quality is categorized as very good for throughput of 5241 Kbps, packet loss of 0%, delay of 136.5 msec, and jitter of 21.28 which are categorized as very good. This study designed a system to make it easier for the elderly as a reminder of the schedule for taking medication as well as a place to store drugs that can maintain the quality of drugs.